CEO Activism and Firm Value - Mkrtchyan, Anahit; Sandvik, Jason; Zhu, Vivi Z. (Management Science, 2024)
We investigate the increasingly common practice of chief executive officers (CEOs) taking public stances on social and political issues (CEO activism). We find that CEO activism stems from a CEO’s personal ideology and its alignment with investor, employee, and customer ideologies. We show that CEO activism results in positive market reactions. Furthermore, firms with CEO activism realize increased shareholdings from investors with a greater liberal leaning, who rebalance their portfolios toward these firms. Our results suggest that investors’ socio-political preferences are an important channel through which CEO activism affects equity demand and stock prices. Notably, CEOs are less likely to be fired when their activist stances generate positive market responses. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.4971 .